Impact of port security implementation on port service quality and customer satisfaction - Chan, Percy Pwee Hong (2015)
Ports play an essential role in the maritime supply chain but there have been a few studies on the security measures in port and their impacts. This paper studies the impact of security regulations of port to Port Service Quality (PSQ) and customer satisfaction specifically. Port security consists of five distinct dimensions, namely physical, personnel, procedural, information technology (IT) and cultural security. The relationship between these five dimensions of port security is drawn to factors of PSQ and customer satisfaction respectively. The PSQ model developed by Thai (2008) was being used in this study. The model was first tested empirically with port operators from the Port of Singapore to confirm the security measures and the PSQ model via interviews. Thereafter, the model was validated through surveys by liner shipping companies, shipping agents, freight forwarders and logistics companies that are customers or likely to be customers of Port of Singapore. In addition, this paper aims to propose several methods that ports could undertake for better transition during the implementation phase of security measures. Regression analysis was conducted using the responses obtained from the surveys. It was found that security implementations (SI) had a positive correlation to both PSQ and customer satisfaction (CS). The strength of the relationship, however, found to be moderate. From further validation, it was found that procedural-related SI and process-related SI were of greater significance among the five dimensions that affect PSQ and CS. SI was discovered, through further analysis, that it had more of an indirect impact on CS rather than a direct one. Based on the findings from working professionals in the port, it was suggested that implementation of security measures should be in phases for a better transition and control. In addition, educating the port workers on the benefits of security measures can allow them to better appreciate and convince them to follow such measures. This paper has attempted to identify the relationship between security implementations on PSQ and customer satisfaction respectively which has not been discussed in the current studies. The paper also supplements the study of SI by providing recommendations on measures for better transition. The drawback of this paper is that it was done in the context of Singapore and specific to the container industry. Future research should focus on other types of terminals in other countries in order to further validate the results. Furthermore, more recommendations on security implementation by working professionals in the port should be obtained.